Global change scenarios trigger carry-over effects across life stages and generations of the intertidal limpet, Siphonaria australis - Kessel, Gustav M. (PLoS One, 2018)
For organisms with complex life histories, carry-over effects (COEs) can manifest between life stages, when conditions experienced by one stage influence the next, as well as trans-generationally, when the parental environment affects offspring. Here we used multiple global change-associated stressors to examine both forms of COE simultaneously in an intertidal limpet with mixed development (i.e. planktonic larvae hatch from benthic egg masses). Adult Siphonaria australis were subjected to four treatments over four weeks: an ambient control, a treatment featuring elevated water temperature (25°C) and UVB (1.7 W m(-2)), a copper pollution treatment (5.0 μg L(-1)), and a treatment incorporating all three stressors. Egg masses laid by these adults were then redistributed among the same four treatments (producing 16 adult-to-egg treatment histories) and stressed until hatching. Finally, hatching larvae were reared under ambient conditions for 24 days. While adult survivorship was unaffected by treatment, embryonic viability in egg masses responded strongly to egg mass treatment, as well as parental stress exposure, therefore displaying trans-generational COEs. These trans-generational COEs interacted with COEs originating in egg masses to produce highly context-dependent hatching sizes and larval growth. This demonstrates that the performance of a given organism at a given time reflects not only conditions experienced during embryonic development, but also those of the parental generation, and suggests that COEs play an important but underestimated role in responses to global change scenarios.